History of the Obesogen Field: Looking Back to Look Forward - Heindel, Jerrold J. (Frontiers in Endocrinology, 2019)
The Obesogen field developed from two separate scientific research areas, endocrine disruptors and the Developmental Origins of Disease. Endocrine disruptors are exogenous chemicals or mixtures that interfere with the action of hormones. Exposures to EDCs during development (in utero and neonatal period in animal models or early childhood in humans) has been shown to increase susceptibility to a variety of diseases including infertility, asthma, breast and prostate cancer, early puberty, susceptibility to infections, heart disease, autoimmune disease, and ADHD/learning disability. The focus on the effects of EDCs on obesity and fat cell development started slowly around the turn of the 21st century. In 2002 Dr. Paula Baillie-Hamilton wrote the first review article focusing on environmental chemicals and obesity. She suggested that the obesity epidemic correlated with the increased production of chemicals after World War II. She identified studies showing that exposures to a variety of chemicals led to weight gain. Shortly thereafter a commentary on an article showing that nonylphenol would increase fat cell differentiation in vitro noted the Baillie-Hamilton article and made the point that perhaps obesity was due to in part to exposure to EDCs. The following year there was a call for research that focused on EDC exposures in utero and diseases later in life. That research call started a focus on EDC exposures in utero and obesity later in life. In 2006 the field of DOHaD/EDCs and obesity got a giant leap forward when Bruce Blumberg, coined the term obesogen for an EDC that could cause weight gain and lead to obesity. This presentation will describe these early days that lead to the obesogen hypotheses and the effect the obesogen hypotheses had on this developing field for a decade leading to its prominence today.